2001
DOI: 10.1159/000049999
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Hypertension, the Role of Genetically Altered Steroid Metabolism

Abstract: The importance of hypertension in the pediatric population is not as well appreciated as in adults. This might be related in part to the lower prevalence of high blood pressure in this age group. As with height and weight, blood pressure increases with age during childhood. The underlying causes of significant hypertension in children differ considerably from those in adults: while the prevalence of hypertension in pediatrics is lower than in adults, clinically identifiable causes of hypertension are common. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 72 publications
(95 reference statements)
0
14
0
1
Order By: Relevance
“…Therefore, we postulate that 11b-HSD2 cannot be restored to normal values by renal transplantation. The reduced activity of 11b-HSD2 leads to an increase in various metabolites inducing salt retention and leading to arterial hypertension (3,5,6,9,10,13,29,31,32). A very strict and aggressive antihypertensive drug therapy is necessary to avoid secondary complications of long-lasting arterial hypertension (12, 21, 33 -35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we postulate that 11b-HSD2 cannot be restored to normal values by renal transplantation. The reduced activity of 11b-HSD2 leads to an increase in various metabolites inducing salt retention and leading to arterial hypertension (3,5,6,9,10,13,29,31,32). A very strict and aggressive antihypertensive drug therapy is necessary to avoid secondary complications of long-lasting arterial hypertension (12, 21, 33 -35).…”
Section: Discussionmentioning
confidence: 99%
“…The isoenzyme 11b-HSD type 1 catalyzes the reverse action from E to F in adipose tissue, human lung and liver (4,7). 11b-HSD2 dysregulation is involved in arterial hypertension in acquired disorders such as hypercortisolism and primary arterial hypertension (8,9). Absolute 11b-HSD2 deficiency is the cause of apparent mineralocorticoid excess (AME), a rare autosomal recessive defect due to a mutation in 11b-HSD2 (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that HSD may modulate the plasma glucocorticoids level, at least partly, via regulating the gene expression of P450 11beta in the cortical cells. Genetic mutations in CYP11B1 gene, which encodes P450 11beta , have been reported to result in hypertension with cortisol deficiency in human (Ferrari et al, 2001). Thus, decrease in the adrenal expression of P450 11beta and the plasma corticosterone in the 4 days HSD group may represent perhaps a short-term effect of extra sodium loading on hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it appears that the extended salt loading, likely as physiological stress, may increase the adrenal expression of P450 11beta by activating the hypothalamicpituitary-adrenal axis. As mentioned above, P450 11beta expression in the adrenal cortex is stimulated by ACTH, a hormone released in response to stress (Ferrari et al, 2001;Sewer and Waterman, 2003). However, no report has shown an increase in plasma ACTH by chronic salt loading.…”
Section: Et Al 2001mentioning
confidence: 93%
“…2,3 Parallel 11b-hydroxylation of the 17-hydroxysteroid, which is catalyzed by the enzyme 11b-hydroxylase encoded by the gene CYP11B1, produces cortisol in the zona fasciculata. 4 CYP11B2 and CYP11B1 are situated B40 kb apart, on chromosome 8, band 8q24 in human. 5 Several frequent polymorphisms in CYP11B2 are suggested to have associations with essential hypertension and may influence aldosterone secretion.…”
Section: Introductionmentioning
confidence: 99%